Criterion and Convergent Validity of the Montreal Cognitive Assessment with Screening and Standardized Neuropsychological Testing. Issue 12 (9th December 2013) - Lam, Benjamin; Middleton, Laura E.; Masellis, Mario; Stuss, Donald T.; Harry, Robin D.; Kiss, Alex; Black, Sandra E.
Abstract : Objectives: To compare the validity of the Montreal Cognitive Assessment (MoCA) with the criterion standard of standardized neuropsychological testing and to compare the convergent validity of the MoCA with that of existing screening tools and global measures of cognition. Design: Cross‐sectional observational study. Setting: Tertiary care hospital‐based cognitive neurology subspecialty clinic. Participants: A convenience sample of 107 individuals with mild Alzheimer's disease (AD, n = 75) or mild cognitive impairment (MCI, n = 32) from the Sunnybrook Dementia Study. Measurements: In addition to the MoCA, all participants completed the Mini‐Mental State Examination (MMSE), the Mattis Dementia Rating Scale (DRS), and detailed neuropsychological testing. Results: Convergent validity was supported, with MoCA scores correlating well with the MMSE (correlation coefficient ( r ) = 0.66, P < .001) and the DRS ( r = 0.77, P < .001) and the MoCA better associated with the DRS than did the MMSE. Criterion validity was supported, with MoCA subscores according to cognitive domain correlating well with analogous neuropsychological tests and, in the case of memory (area under the receiver operating characteristic curve (AUC) = 0.86), executive (AUC = 0.79), and visuospatial function (AUC = 0.79), being reasonably sensitive to impairment in those domains. Conclusion: The MoCA is a valid assessment of cognition that shows good agreement with existing screening tools and global measures (convergent validity) and was superior to the MMSE in this regard. The MoCA domain‐specific subscores align with performance on more‐detailed neuropsychological tests, suggesting not only good criterion validity for the MoCA, but also that it may be useful in guiding further neuropsychological testing.